The The Impact of Work Value and Satisfication on Employee Engagement at Lazismu Sunggal Service Office - Khairunnisa, Rahma; Lubis, Muhammad Arifin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study examines the impact of work values ​​and job satisfaction on employee engagement at the Lazismu Sunggal service office. This study aims to address the problem of low employee engagement in this social service organization, which is very important to achieve organizational goals and improve employee performance. This study uses a qualitative research design with a case study approach, focusing on employees who have worked at Lazismu Sunggal for at least one year. Data were collected through semi-structured interviews with 3 employees, observation, and documentation. The findings of the study indicate a significant relationship between work values, job satisfaction, and employee engagement. Employees who align their work values ​​with organizational goals tend to be more satisfied and engaged in their jobs. This study concludes that increasing work values ​​and job satisfaction can significantly increase employee engagement, thereby contributing to the effectiveness and efficiency of the organization in managing zakat, infaq, and shadaqah funds.